MENINGKATKAN KESTABILAN KESEHATAN MENTAL DAN SPIRITUAL UNTUK MENGHADAPI TANTANGAN HIDUP MODERN DALAM PERSPEKTIF KRISTEN - Junardi Saleleubaja; Sugeng Santoso (Sekolah Tinggi Teologi Excelsius, 2024)
This article aims to explore the importance of enhancing the balance of mental and spiritual health in facing modern life's challenges, with an emphasis on the Christian perspective. This study employs a descriptive qualitative method through a literature review, analyzing literature related to mental and spiritual health from a Christian perspective. The findings indicate that mental health in Christianity is not only related to emotional and psychological stability but is also integrated with spiritual health. Spiritual health is defined as a deep relationship with God, which provides strength and direction in facing challenges. The interaction between mental and spiritual health shows that these two aspects influence and support each other. This article also highlights the life challenges faced in the Christian context and proposes practical strategies to enhance the stability of mental and spiritual health through prayer, meditation, and Bible reading. This study offers the perspective that improving the stability of mental and spiritual health is essential in Christian life, especially in facing the challenges of modern times.